Modified gel preparation for distinct DNA fragment analysis in agarose gel electrophoresis - Lee, S. V.; Bahaman, Abdul Rani (Malaysian Society of Parasitology and Tropical Medicine, 2010)
Agarose gel electrophoresis is the standard method that is used to separate,identify, and purify DNA fragments. However, this method is time-consuming and capable of separating limited range of fragments. A new technique of gel preparation was developed to improve the DNA fragment analysis via electrophoresis.